22q11.2 microdeletion and increased risk for type 2 diabetes. (September 2020) - Van, Lily; Heung, Tracy; Malecki, Sarah L.; Fenn, Christian; Tyrer, Andrea; Sanches, Marcos; Chow, Eva W.C.; Boot, Erik; Corral, Maria; Dash, Satya; George, Susan R.; Bassett, Anne S.
Abstract: Background: The 22q11.2 microdeletion is the pathogenic copy number variation (CNV) associated with 22q11.2 deletion syndrome (22q11.2DS, formerly known as DiGeorge syndrome). Familiar endocrinological manifestations include hypoparathyroidism and hypothyroidism, with recent elucidation of elevated risk for obesity in adults. In this study, we aimed to determine whether adults with 22q11.2DS have an increased risk of developing type 2 diabetes (T2D). Methods: We studied the effect of the 22q11.2 microdeletion on risk for T2D, defined by history and glycosylated hemoglobin (HbA1c), using weighted survey data from the adult Canadian population (based on n  = 11, 874) and from a clinical cohort of adults with 22q11.2DS ( n  = 314), aged 17–69 years. Binomial logistic regression models accounted for age, sex, non-European ethnicity, family history of T2D, obesity, and antipsychotic medication use. Findings: The 22q11.2 microdeletion was a significant independent risk factor for T2D (OR 2·44, 95% CI 1·39–4·31), accounting for other factors ( p < 0·0001). All factors except sex were also significant within 22q11.2DS. The median age at diagnosis of T2D was significantly younger in 22q11.2DS than in the Canadian population sample (32 vs 50 years, p  < 0·0001). In adults without T2D, HbA1c was significantly higher in 22q11.2DS than the population ( p  = 0·042), after accounting for younger age of the 22q11.2DS group. Interpretation: The results support the 22q11.2 microdeletion as a novel independent risk factor and potential model for early onset T2D. The findings complement emerging evidence that rare CNVs may contribute to risk for T2D. The results have implications for precision medicine and research into the underlying pathogenesis of T2D.